Preserving process: conservation of a Helen Frankenthaler maquette for Card. Issue 1 (3rd April 2018) - Nichols, Kimberly J.; Sorokin, Yelizaveta; Sutherland, Ken; Daher, Céline
ABSTRACT: Contemporary American print publishers, such as Universal Limited Art Editions (ULAE), collaborate with artists to produce prints using high quality materials for their editions. However, for developing their imagery, artists often use more affordable materials that may be prone to degradation, discoloration, and structural instability. This article discusses the treatment of a maquette by Helen Frankenthaler, a multi-layered assemblage of paper and transparent film joined together with pressure-sensitive tape that is one of the several preliminary works for her 1971 lithograph Card, now in the collection of The Art Institute of Chicago. Treatment of the maquette was undertaken to reduce degraded tape adhesive and replace it with a stable pressure-sensitive alternative while preserving the integrity of the work and its original materials. FTIR analysis in reflectance and transmittance modes identified the transparent films as cellulose acetate and the tape carriers as both cellulose acetate and regenerated cellulose (cellophane); these findings informed treatment and storage decisions. An analytical survey of several works in the ULAE collection also confirmed the use of cellulose acetate in works by other artists from the 1960s and 1970s. Therefore, concerns for the stability of this material would ultimately factor into the broader preservation plan for the archive.